(untitled) (Research, Society and Development, 2025)
Autism Spectrum Disorder (ASD) is characterized by difficulties in communication, social interaction, and repetitive or restricted behaviors. Diagnosis can occur as early as the first year of life, but autistic girls often receive a late diagnosis due to symptoms that differ from the expected patterns. This is because diagnostic instruments, based on the DSM-5, have a male bias, making it difficult to identify ASD in girls and impacting their psychosocial development. The study aims to identify the particularities of ASD in girls and adolescents aged 0 to 19 years. This study, an integrative review, analyzed the particularities of ASD in girls and adolescents aged 0 to 19 years, considering articles published between 2020 and 2024 in the BVS, Cochrane, PUBMED, and SciELO databases. Nine articles were selected, following the PRISMA flowchart. A striking characteristic of female ASD is “camouflage,” a strategy that allows girls to mask behaviors and adapt to social norms. Although it facilitates interaction, this practice is exhausting, harms mental health and delays diagnosis. Studies show that girls with ASD have greater social attention and more adjusted behaviors in childhood, but develop difficulties such as anxiety and less eye contact. Brain differences have also been identified, such as slower reduction of gray matter and lower presence of ASD biomarkers, suggesting protective mechanisms in females. These findings reinforce that autism manifests itself differently between the sexes, and a diagnostic model based on males can lead to underdiagnosis and lack of adequate support for autistic girls.